Desarrollo de películas de almidón oxidado de cáscaras de plátano verde y aceite esencial de cáscaras de naranja - Toapanta Román, Steeven Fernando (My University, 2024)
Environmental pollution caused by disposable plastics has generated a global crisis, driving the search for biodegradable alternatives. This experimental work addresses this problematic development of biodegradable films from starch extracted from green banana peels, an abundant agricultural residue, and essential oil from orange peels. The starch extraction process was carried out using wet grinding and avoiding enzymatic browning with citric acid (C6H8O7), obtaining a yield of 4.5166±1.3614%. The chemical modification used was the oxidation method, applied to starches extracted from banana peels; for the formulation of oxidized starches, it was started with a standard concentration of 0.5% NaClO (v/v) with active chlorine and reaction times of 30 and 45 minutes, demonstrating that the reaction increased the carboxyl groups (p<0.05). The functional properties analyzed such as water absorption index (WAI), water solubility index (WSI) and swelling power (PH), analyzed in oxidized starches, tend to increase as reaction times increase (p<0.05). The chemical composition of the starches studied registered an increase in the percentages of ash, moisture (p<0.05); but the opposite is shown in the percentages of proteins, fats, fibers and carbohydrates (p<0.05). The formulation of the films was developed through a multilevel factorial design, of 2², developed in three blocks, using the Statgraphics 19 program, obtaining a total of 12 treatments with two levels of glycerol of 2% w/w and 3% w/w and AE. of orange peels with two levels of (0.3% w/w and 0.6% w/w); keeping the starch and water contents constant; The proposed response variables were %Humidity, %Solubility and PVA. The percentage of essential oil (EO) from orange peel residues and its interaction with the percentage of glycerol plasticizer, tend to decrease the % of humidity, %solubility and PVA of the films studied (p<0.05); while the percentage of glycerol alone tends to increase the percentages of the response variables studied in the films obtained (p<0.05). The optimal values for the formulation of films with glycerol and EO from orange peel that facilitate minimizing the % of humidity and % solubility were 2%w/w and 0.69%w/w, respectively and for PVA, the optimal values that allow minimizing this response variable were 3%w/w and 0.29%w/w; these percentages reduce the physical properties of humidity and solubility; as well as the barrier properties of PVA. Finally, the adjusted model of the response variables obtained for %humidity, %solubility and PVA indicate an R² of 99.7822%, 99.5528% and 98.2412% and the adjusted R² of 99.6008%, 99.1802% and 96.7755% respectively and their regression models obtained were, (%Humidity= 3.41667 + 4.46333 * %Glycerol + 7.13333 * %AE6.05556 * %Glycerol * %AE), (%Solubility= 0.517533 + 0.181033 * %Glycerol - 0.0412222 * %AE - 0.226333 * lycerol * %AE) and (%PVA= -0.000403716 + 0.000211928 * %Glycerol + 0.000670489 * %AE - 0.000343409 * %Glycerol * %AE).
La contaminación ambiental causada por plásticos desechables ha generado una crisis global, impulsando la búsqueda de alternativas biodegradables. Este trabajo experimental, aborda esta problemática desarrollando películas biodegradables a partir de almidón extraído de cáscaras de plátano verde, un residuo agrícola abundante, y aceite esencial de cáscaras de naranja. Se llevó a cabo el proceso de extracción del almidón empleando la molienda húmeda y evitando el pardeamiento enzimático con ácido cítrico (C6H8O7), obteniendo un rendimiento de 4.5166±1.3614%. La modificación química empleada fue el método de oxidación, aplicado a los almidones extraídos de las cáscaras de plátanos; para la formulación de los almidones oxidados, se inició con una concentración estándar de 0.5% de NaClO (v/v) con cloro activo y tiempos de reacción de 30 y 45 minutos, demostrando que la reacción incrementó los grupos carboxilos (p<0.05). Las propiedades funcionales como el índice de absorción de agua (IAA), el índice de solubilidad en agua (ISA) y el poder de hinchamiento (PH), analizados en los almidones oxidados, tienden a incrementar a medida que aumentan los tiempos de reacción (p<0.05). La composición química de los almidones estudiados registró incremento en los porcentajes de cenizas, humedad (p<0.05); pero se demostró lo contrario en los porcentajes de proteína, grasa, fibra y carbohidratos. (p<0.05). La formulación de las películas se desarrolló mediante un diseño factorial multinivel, de 2², desarrollado en tres bloques, empleando el programa Statgraphics 19, obteniendo un total de 12 tratamientos con dos niveles de glicerol de (2%p/p) y (3%p/p) y AE de cáscaras de naranjas con dos niveles de (0.3%p/p y 0.6%p/p); manteniendo constante los contenidos de almidón y agua; las variables de respuestas propuestas fueron %Humedad, %Solubilidad y PVA. El porcentaje de aceite esencial (AE) de residuos de cáscaras de naranja y su interacción con el porcentaje de plastificante glicerol, tienden a disminuir los %Humedad, %Solubilidad y PVA de las películas estudiadas (p<0.05); mientras que el porcentaje de glicerol por sí solo tiende a incrementarse en los porcentajes de las variables de respuesta estudiadas en las películas obtenidas (p<0.05).Los valores óptimos para la formulación de películas con glicerol y AE de cáscara de naranja que facilitan minimizar el %Humedad y el %Solubilidad fueron de (2%p/p) y (0.69%p/p), respectivamente y para la PVA, los valores óptimos que permiten minimizar esta variable de respuesta fueron de (3%p/p) y (0.29%p/p); estos porcentajes reducen las propiedades físicas de humedad y solubilidad, así como las propiedades de barrera del PVA. Por último, el modelo ajustado de las variables de respuesta obtenidas para él %Humedad, %Solubilidad y PVA indicadas por las R² ajustadas de 99.6008%, 99.1802% y 96.7755% respectivamente y sus modelos de regresión obtenidos fueron, (%Humedad= 3.41667 + 4.46333 * %Glicerol + 7.13333 * %AE6.05556 * %Glicerol * %AE), (%Solubilidad= 0.517533 + 0.181033 * %Glicerol - 0.0412222 * %AE - 0.226333 * %Glicerol * %AE) y (%PVA= -0.000403716 + 0.000211928 * %Glicerol + 0.000670489 * %AE - 0.000343409 * %Glicerol * %AE).
Keywords: BIODEGRADABLES; ALMIDON OXIDADO; CASCARA DE PLATANO; ACEITE ESENCIAL